Urbino, ou l’histoire des relations de coévolution entre un établissement humain et son milieu naturel - Roberta Morelli (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the field of architecture, the finiteness of resources is a generally accepted observation and, in recent years, has given rise to a multitude of debates and practices, albeit not without ambiguities. This article hypothesizes that rethinking the relationship to the Earth’s resources means both reevaluating the interdependence between anthropogenic action and the natural environment, as well as identifying the necessary conditions for the interaction of the material and immaterial dimensions of the notion of resource. It does so through a discussion of the architectural and urban history of the city of Urbino, Italy, as well as the reflections and actions of the people who have marked its development. Apparently far removed from current environmental concerns, this history – and in particular the urban transformation processes carried out in the 15th and 20th centuries – testifies to a process of coevolution balanced between humankind and their environment, and can help to revise ways of thinking about the transformation of human settlement from a sustainable perspective.